A genetic study of a Brazilian cohort of patients with X-linked hypophosphatemia reveals no correlation between genotype and phenotype - Borghi, Mauro; Silva, Leopoldo Muniz da; Bispo, Luciana; Longui, Carlos A. (Frontiers in Pediatrics, 2023)
Aim: X-linked hypophosphatemia (XLH) is the most common inherited form of rickets and it is caused by pathogenic inactivating variants of the PHEX gene. The main purpose of this study was to recognize the presence of genotype-phenotype correlation in a cohort of XLH patients. Methods: This is a retrospective study including patients with hypophosphatemic rickets with the diagnosis confirmed by clinical, radiological, and laboratory findings. Medical records were reviewed for phenotypic analyses. Genomic DNA was extracted from the peripheral blood lymphocytes and PHEX sequencing was performed by exomic NGS sequencing. The Wilcoxon rank-sum test and the two-tailed Fisher’s exact test were employed for statistical analyses. Results: Forty-one patients were studied; 63.41% (26/41) were female. Mutation analyses identified 29.27% missense and 29.72% nonsense variants, most of them were considered deleterious (66.41%). Six novel deleterious variants in the PHEX gene were detected in seven patients. The median of pre-treatment serum calcium, phosphorus, and PTH concentrations were not significantly different among patients with different genotypes. Orthopedic surgery due to bone deformity was required in 57.69%. Conclusions: Our analysis did not identify any specific genotype as a predictor. No significant genotype-phenotype correlation was found, suggesting that the recognition of subjacent pathogenic mutation in the PHEX gene may have limited prognostic value. Despite of this, genetic testing may be useful for early identification and treatment of affected individuals.